Knockdown of annexin A2 enhances the host cell apoptosis induced by Eimeria tenella - Wang, Jixia; Wang, Mingxiao; Wang, Yuting; Xu, Mengbo; Liu, Yang; Zheng, Mingxue; Zhao, Rui; Bai, Rui; Zhao, Yanping; Zhang, Li; Lv, Xiaoling; Yang, Yu; et al. (Frontiers in Veterinary Science, 2025)
Annexin A2 (ANXA2) is a multifunctional protein involved in host-pathogen interactions during viral and parasitic infections. To investigate the role of ANXA2 in host cell apoptosis induced by Eimeria tenella, RNA interference (RNAi) was employed to specifically downregulate ANXA2 expression. Primary cultures of chicken embryonic cecal epithelial cells were established and subjected to E. tenella sporozoite infection. A comprehensive analytical approach integrating hematoxylin-eosin staining, Hoechst-Annexin V-PI triple-staining, and caspase-3 activity quantification was used. Western-blot and RT-qPCR were performed to assess transcriptional and translational changes in key apoptosis-related factors, including B-cell lymphoma (Bcl-2) and Bcl-2-associated X protein (Bax). Additionally, the dynamic expression of ANXA2 was analyzed to clarify its function in the parasite-host interaction. The results showed that the ANXA2 expression in the E. tenella group increased at 4 h after inoculation but decreased at 24 to 96 h compared to the control group (P < 0.01). Following ANXA2 knockdown, the cell apoptosis rate, caspase-3 activity, and Bax expression levels were significantly increased (P < 0.01), whereas the infection rate and Bcl-2 expression levels were significantly decreased (P < 0.01) compared to the group infected with E. tenella alone. In conclusion, ANXA2 serves as a critical regulator of host cell responses during E. tenella infection. RNAi-mediated suppression of ANXA2 expression significantly enhances apoptosis induced by E. tenella. This study establishes a foundation for further exploration of therapeutic targets to reduce host tissue damage, indicating that targeting ANXA2 may be a viable approach for controlling coccidiosis.